Prospek Cu pada Vulkanogenik Masif Sulfida (VMS) Daerah Pit X, Pulau Wetar Menggunakan Data Bor - Titawael, Grace Vebiola; Trianda, Obrin; Nugrahini, Amara (Retii, 2024)
Pit X area is located on Wetar Island which is included in the Southwest Maluku region, this research was conducted in the PT Batutua Kharisma Permai (Merdeka Copper Gold) area. The research focuses on geological conditions as well as exploration and copper levels (VMS) in the Company. The method used is direct observation in the field as well as studio and laboratory analysis. Geologically, Wetar Island was formed in the Tertiary-Quaternary period due to the collision of two plates, namely the Indian-Australian plate and the Eurasian plate, included in the inner banda arc zone. Included in the Naumatan and Alor formations, the general geological structure is faults and folds. VMS (Volcanic Massive Sulfide) are deposits of base metal sulfide minerals associated with volcanism related to hydrothermal processes in submarine environments (Hutchinson, 1973). The formation of VMS is caused by rifting / mini wetar basin opening alteration and mineralization pathways causing the formation of Black smoker Cu enrichment (Sulfide mound) to White Smoker (Barite, Au). From the use of drill data and cross sections, the results of potential ore content averaged Cu 0.62 - 3.28%, Au 0.28 - 0.77 g/t, and Ag 0.1 - 37.6 g/t and Zn 0.25% and cross section B Cu 0.52 - 2.41%, Au 0.39 - 0.72 g/t, Ag 5.2 - 22.3 g/t, Zn 0.48% and Pb 0.24%. QAQC data shows copper (Cu) prospects in both cross sections with an average content of 1.3% - 1.5% with a difference of 0.2%. Has a relatively favorable Cu prospect direction north-south Cu of 0.6% - 3.3% or equivalent to 6000-33000 ppm.